KHIDMAH; STUDENT DEVOTION TO THE TEACHER (A Brief Review) - Najah, Ahmadun (Journal Intellectual Sufism Research (JISR), 2021)
One of the distinctive cultures that live sustainably in the boarding school environment is the khidmah tradition. Khidmah is interpreted as an attitude and wholehearted devotion activity carried out by a santri to his kyai or teacher, both during the study period at the boarding school or after graduation. Among Islamic boarding schools, this khidmah tradition has been deeply rooted since ancient times and is still maintained until now, and it is felt that it will persist into the future. More than just a tradition, this khidmah becomes an important identity of a santri as well as one of the benchmarks for his success in studying because in Islamic boarding school education. This study tries to explain the meaning and forms of khidmah, the factors behind the emergence of khidmah, motivation for khidmah, the theological basis of khidmah, as well as its virtues and benefits so that people can understand this khidmah problem more deeply and completely. This research is qualitative in the form of a literature study, with a conceptual approach to Sufism and morality. So it is possible to answer some aspects of the problem as mentioned earlier. After extracting the data and analyzing it, in this study several conclusions were obtained, including; first, khidmah is a form of devotion and service performed by a student (santri) to his teacher (kyai), as a form of respect and obedience to the teacher. This devotion can be in the form of devotion that has physical nuances, thoughts, possessions, or in the form of prayer. Second, the emergence of a khidmah tradition in Islamic boarding schools and other Islamic educational institutions is motivated by several factors such as strong moral education, especially morals for teacher (kyai), kyai who is believed to be pious and holy people, and the dormitory life system in the community a long period which builds an inner closeness between teacher and student. Third, some of the motivations that encourage students to be khidmah are to get the kyai's willingness (ridha) as well as an expression of gratitude and want to repay the kyai's services..